1997
DOI: 10.1111/j.1471-0528.1997.tb11051.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of gestational diabetes with abnormal maternal vascular endothelial function

Abstract: .0], P < 0.01). In the presence of indomethacin relaxation to acetylcholine was similar in both groups suggesting a deficiency in dilator rostaglandin synthesis in further reduced sensitivity of arteries to acetylcholine but to a similar degree in both normal pregnant and gestational diabetic women. Relaxation to sodium nitroprusside, an indicator of sensitivity of the vascular smooth muscle to nitric oxide, was similar in both groups.Conclusions Maternal vascular endothelial dysfunction may contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 29 publications
2
58
0
5
Order By: Relevance
“…Indeed, sICAM1 and sVCAM1 levels are higher in insulin resistance, obesity and type 2 diabetes (Guler et al 2002, Leinonen et al 2003, Kent et al 2004. There is also evidence indicating that women with GDM develop endothelial dysfunction during pregnancy (Knock et al 1997), and despite returning to NGT, endothelial dysfunction is still evident in women 1-year post GDM pregnancy (Pleiner et al 2007). Indeed, women with GDM have increased circulating sICAM1 and sVCAM1 levels (Mordwinkin et al 2013).…”
Section: Figurementioning
confidence: 99%
“…Indeed, sICAM1 and sVCAM1 levels are higher in insulin resistance, obesity and type 2 diabetes (Guler et al 2002, Leinonen et al 2003, Kent et al 2004. There is also evidence indicating that women with GDM develop endothelial dysfunction during pregnancy (Knock et al 1997), and despite returning to NGT, endothelial dysfunction is still evident in women 1-year post GDM pregnancy (Pleiner et al 2007). Indeed, women with GDM have increased circulating sICAM1 and sVCAM1 levels (Mordwinkin et al 2013).…”
Section: Figurementioning
confidence: 99%
“…This is surprising since the disorder is characterised by insulin resistance, inability to increase output of insulin (Bowes et al, 1996), impaired glucose transport and insulin receptor autophosphorylation (Friedman et al, 1999;Yamashita et al, 2000) and vascular endothelial dysfunction (Knock et al, 1997). Abnormalities of plasma (Wijendran et al, 1999) and red cell (Wijendran et al, 2000) fatty acids have been reported in diettreated GDM women.…”
Section: Introductionmentioning
confidence: 99%
“…Knock et al (13) reported impaired endothelial response to acetylcholine in small artery rings of pregnant women with gestational diabetes. Other authors found defective endothelium-dependent vasodilatation in euglycemic women with previous GDM (7).…”
Section: Conclusion -mentioning
confidence: 99%